Perception of Government Employees at the Food Security Office of Bali Province on Cultural Shifts Due to Digital Shifting - Komang Arie Putri Triyandani; Gede Sri Darma (Faculty of Law, Universitas Pekalongan, 2024)
Digital transformation that occurs in the industrial revolution 4.0 brings significant changes in various sectors, including local governments in Indonesia such as the Bali Province Food Security Office. Digital shifting affects the way of operation, interaction with the community, and organizational culture. This study aims to understand the perceptions of Denpasar City government employees regarding digital shifting. Data was collected through a pre-survey and interviews with a focus on technology use, changes in work patterns, digital training, and impact on employment. The findings show that there is an awareness of the importance of adapting to technological change, but also a concern of job loss due to digital shifting. Understanding these perceptions can help the government design policies that support adaptation to digital transformation while mitigating its negative impacts.